Bronchopulmonary dysplasia as a determinant of respiratory outcomes in adult life. Issue 11 (17th March 2021) - Collaco, Joseph M.; McGrath‐Morrow, Sharon A.
Abstract: Respiratory disease is unfortunately common in preterm infants with the archetype being bronchopulmonary dysplasia (BPD). BPD affects approximately 50, 000 preterm infants in the U.S. annually with substantial morbidity and mortality related to its pathology (alveolar, airway, and pulmonary vasculature maldevelopment). Predicting the likelihood and severity of chronic respiratory disease in these children as they age is difficult and compounded by the lack of consistent phenotyping. Barriers to understanding the actual scope of this problem include few longitudinal studies, information limited by small retrospective studies and the ever‐changing landscape of therapies in the NICU that affect long‐term respiratory outcomes. Thus, the true burden of adult respiratory disease caused by premature birth is currently unknown. Nevertheless, limited data suggest that a substantial percentage of children with a history of BPD have long‐term respiratory symptoms and persistent airflow obstruction associated with altered lung function trajectories into adult life. Small airway disease with variable bronchodilator responsiveness, is the most common manifestation of lung dysfunction in adults with a history of BPD. The etiology of this is unclear however, developmental dysanapsis may underlie the airflow obstruction in some adults with a history of BPD. This type of flow limitation resembles that of aging adults with chronic obstructive lung disease with no history of smoking. It is also unclear whether lung function abnormalities in people with a history of BPD are static or if these individuals with BPD have a more accelerated decline in lung function as they age compared to controls. While some of the more significant mediators of lung function, such as tobacco smoke and respiratory infections have been identified, more work is necessary to identify the best means of preserving lung function for individuals born prematurely throughout their lifespan.